2018
DOI: 10.1002/anie.201710698
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phenols: Organophotoredox/Nickel Dual Catalytic Hydroxylation of Aryl Halides with Water

Abstract: A highly effective hydroxylation reaction of aryl halides with water under synergistic organophotoredox and nickel catalysis is reported. The OH group of the resulting phenols originates from water, following deprotonation facilitated by an intramolecular base group on the ligand. Significantly, aryl bromides as well as less reactive aryl chlorides served as effective substrates to afford phenols with a wide range of functional groups. Without the need for a strong inorganic base or an expensive noble-metal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 65 publications
2
50
0
1
Order By: Relevance
“…Recently, we reported a hydroxylation reaction of aryl halides with water enabled by the merger of organophotoredox and nickel catalysis with mildly basic N , N ‐diisopropylethylamine as a base . Our study showed that only organic amines can promote the reaction, with traditional strong bases such as NaO t Bu and inorganic bases being ineffective.…”
Section: Methodsmentioning
confidence: 88%
“…Recently, we reported a hydroxylation reaction of aryl halides with water enabled by the merger of organophotoredox and nickel catalysis with mildly basic N , N ‐diisopropylethylamine as a base . Our study showed that only organic amines can promote the reaction, with traditional strong bases such as NaO t Bu and inorganic bases being ineffective.…”
Section: Methodsmentioning
confidence: 88%
“…Processes such as the Vilsmeier-Haack formylation followed by Dakin oxidation, [5] and the Hock process, [6] are used to synthesize phenols on an industrial scale. Transition metal-promoted reactions, [3] such as the Sandmeyer hydroxylation, [7] Ullmann-type reactions, [8] Chan-Lam couplings, [9] palladium-catalyzed CÀO bond forming reactions, [10] and various others, [11][12][13] have been developed to install C À O bonds. Most of the transition metal-promoted reactions are performed on aryl halides or arylboronic acids, and are robust transformations for phenol and aryl ether synthesis.…”
mentioning
confidence: 99%
“…Several pharmaceuticals were hydroxylated siteselectively (1,6,11,16,21,25,26). Occasionally, the hydroxylation of alkyl substituted arenes can be problematic in the sense that hydrodefunctionalized sideproducts are formed with Cu 2 O; in such cases copper(I) thiophene-2carboxylate (CuTC) could be used successfully to circumvent the problem to give the desired phenols (5,10,12,14,19,23) in higher yields.…”
mentioning
confidence: 99%
“…1113 Thermolysis of Ni(II) oxametallacycles, for example, results in β-hydride elimination of undesired carbonyl compounds, whereas oxidation to Ni(III) complexes via single electron transfer (SET) with stoichiometric oxidants can induce reductive elimination resulting in C–O bond formation. 14 Combining nickel with photoredox catalysis, 1517 enables the coupling of aryl bromides with alcohols 18,19 or water 20 without stoichiometric SET oxidants.…”
mentioning
confidence: 99%